Особенности осморегулирующей функции почек у больных с сахарным диабетом 1 типа = Features of the renal osmoregulatory function in patients with type 1 diabetes - Kuznetsova, E. S.; Kuznetsova, E. N.; Shuhtin, V. V.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2015)
Kuznetsova E. S., Kuznetsova E. N., Shuhtin V. V., Gozhenko A. I. Особенности осморегулирующей функции почек у больных с сахарным диабетом 1 типа = Features of the renal osmoregulatory function in patients with type 1 diabetes. Journal of Education, Health and Sport. 2015;5(8):64-72. ISSN 2391-8306. DOI 10.5281/zenodo.23452 http://dx.doi.org/10.5281/zenodo.23452 https://pbn.nauka.gov.pl/works/603458 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-723295be-1b7a-4fb7-977a-b926e021635b http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A64-72 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. УДК 616.43;616-008.9 Особенности осморегулирующей функции почек у больных с сахарным диабетом 1 типа Features of the renal osmoregulatory function in patients with type 1 diabetes Е. С. Кузнецова, Е. Н. Кузнецова, В. В. Шухтин, А. И. Гоженко E. S. Kuznetsova, E. N. Kuznetsova, V. V. Shuhtin, A. I. Gozhenko Украинский научно – исследовательский институт медицины транспорта МЗ Украины, Одесса Ukrainian Scientific Research Institute of Transport Medicine MH Ukraine, Odessa Abstract In the context of water - salt load with 0,5% NaCl the osmoregulatory renal function state in 28 patients with type 1 diabetes. It is shown that as the GFR declines to 60 ml \ min the diuresis and % of the discharged liquid increases from 176 ml and 46.1% to 213 ml and 59.5%, while the relative density of urine and osmolality, conversely, decreases. A direct relationship was observed between diuresis and excretion of osmotically active substances (correlation coefficient 0.76 - 0.91), between excretion of osmotically active substances and % of the discharged liquid (0.8 - 0.91), between the relative density and urine osmolality (0.85 - 0.9), between excretion of osmotically active substances (OAS) and glycosuria: thus, maximum excretion of OAS of 224.1 and 345 mOsmol \ hour was combined with glycosuria of 210 and 220 mmol/l. In most of cases (96.4%), glomerular filtration rate averagely increased 2-fold in patients with diabetes 1 type under water - salt stress, rising from 36.9 to 322.5 ml \ min, and renal functional reserve ranged from 36.9 to 439.6%. However, a direct relationship between the RFR and urine osmolality, as well as with an osmotically active substances excretion, was not found. Thus, in type 1 diabetes osmoregulatory renal disorders depend both on the reduction in GFR to 60 ml \ min and on changes in the functional capacity of nephron`s tubules. Key words: diabetes mellitus type 1, osmoregulatory function state of kidneys, water- salt load, excretion of osmotically active substances, renal functional reserve. Резюме В условиях водно- солевой нагрузки с 0,5 % NaCl изучено состояние осморегулирующей функции почек у 28 больных с сахарным диабетом 1 типа. Показано, что по мере снижения СКФ до 60 мл\мин, диурез и % выделенной жидкости возрастали с 176 мл и 46,1 % до 213 мл и 59,5 % , при этом относительная плотность мочи и осмоляльность, наоборот, снижались. Прямая взаимосвязь наблюдалась между диурезом и экскрецией осмотически активных веществ (коэффициент корреляции 0,76 - 0.91), между экскрецией осмотически активных веществ и % выделенной жидкости (0.8 - 0,91), между относительной плотностью и осмоляльностью мочи (0.85 до 0,9) и между экскрецией осмотически активных веществ и глюкозурией: так, максимальная экскреция ОАВ 224,1 и 345 мосмоль\час наблюдалась при глюкозурии 210 и 220 ммоль\л. В большинстве случаев (96,4 %) скорость клубочковой фильтрации у больных с СД 1типа в условиях водно-солевой нагрузки возрастала, в среднем в 2 раза, повышаясь от 36,9 до 322,5 мл\мин, а функциональный почечный резерв находился в пределах от 36,9 до 439,6 %. Однако прямой взаимосвязи между величиной ФПР и осмоляльностью мочи, так же как и с экскрецией осмотически активных веществ не было. Таким образом, при сахарном диабете 1 типа появляются нарушения осморегулирующей функции почек, которые возникают как по мере уменьшения СКФ до 60 мл\мин, так и при изменении функциональной способности канальцев нефронов. Ключевые слова: сахарный диабет 1 тип, осморегулирующая функция почек, водно-солевая проба, эксреция осмотически активных веществ, функциональный почечный резерв.